Odpowiedzi

2010-03-17T22:05:29+01:00
A) 2(x+3) - 5 > -2x - 7
2x+6-5>-2x-7
2x+1>-2x-7 /-1
2x>-2x-8 /+2x
4x>-8 /:4
x>-2

b) -2(x+1) + 5x > 7x + 12
-2x-2+5x>7x+12
3x-2>7x+12 /+2
3x>7x+14 /-7x
-4x>14 /:(-4)
x<-3,5 (przy dzieleniu przez liczbę minusową, zmieniamy zwrot nierówności)

c) ⅓x + 1 > -x + 2 /+x
1⅓x+1>2 /-1
1⅓x>1 /:1⅓
x>¾

d) 0,7x - 2 ≤ 0,9x - 0,1 /-0,9x
-0,2x-2≤-0,1 /+2
-0,2x≤1,9 /:(-0,2)
x≥-9,5

e) -x + 3 ≥ -(3x - 2)
-x+3≥-3x+2 /-3
-x≥-3x-1 /+3x
2x≥-1 /:2
x≥-½

f) 0,1(2x - 3) < -0,6 + 1
0,2x-0,3<0,4 /+0,3
0,2x<0,7 /:0,2
x<3,5
4 2 4